2019
DOI: 10.1080/21663831.2019.1596989
|View full text |Cite
|
Sign up to set email alerts
|

Laser deposition additive manufacturing of 17-4PH stainless steel on Ti-6Al-4V using V interlayer

Abstract: For the first time, additive manufacturing was used to obtain a strong joint (bonding strength > 200 MPa) between stainless steel and Ti-6Al-4V using a V interlayer. The V interlayer applied via solid-state joining prevented the formation of brittle intermetallic phases more effectively than a V interlayer deposited by a liquid-state process. The microstructure and strength of the joint interface depended on the laser power and scan speed. The joint strength decreased with increasing annealing time, especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 18 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…It can be seen from the figure that the black spots are composed of all elements from the alloy coating and substrate, including Co, Cr, Ni, Mo, Fe, and C. This may indicate that the spots are formed by incomplete melting and rapid solidification during the coating process. A study by Adomako et al [25] found that the higher the scanning speed, the shorter the laser heating/melting time, resulting in an incomplete melting of the powder, which coupled with rapid solidification and resulted in the formation of pores, in consistency with our conclusion.…”
Section: Morphologiesof the Composites Coatingssupporting
confidence: 92%
“…It can be seen from the figure that the black spots are composed of all elements from the alloy coating and substrate, including Co, Cr, Ni, Mo, Fe, and C. This may indicate that the spots are formed by incomplete melting and rapid solidification during the coating process. A study by Adomako et al [25] found that the higher the scanning speed, the shorter the laser heating/melting time, resulting in an incomplete melting of the powder, which coupled with rapid solidification and resulted in the formation of pores, in consistency with our conclusion.…”
Section: Morphologiesof the Composites Coatingssupporting
confidence: 92%
“…These could neither be referred to as pores nor as (Fe,Cr) 23 C 6 carbides associated with sensitization [ 40 ]. Intermetallic sigma (σ) phases [ 41 , 42 ], massive transformation [ 43 ], and δ-ferrite can be ruled out too either from compositional or shape considerations. Hence, we believe that the zones described in (b) result from local chemical inhomogeneity during the deposition process.…”
Section: Resultsmentioning
confidence: 99%
“…Type of intermetallic phases that formed in AM joints were similar to those that formed in solid-state weldments [142]. Compositionally gradient Ti-6Al-4 V/Ti-V/304L SS [143] and Ti-6Al-4 V/Ti-V/17-4 PH SS [144] AM joints had marginally higher bond strength than direct deposits whereas through a new graded composition route, Ti-6Al-4 V/V/Cr/Fe/316 SS, brittle intermtallics are reported to be successfully eliminated [145,146].…”
Section: Solid-state Welding Of Fe/ti Alloysmentioning
confidence: 99%